2017
DOI: 10.1016/j.bbi.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome modulates sleep and NREM sleep delta power induced by spontaneous wakefulness, sleep deprivation and lipopolysaccharide

Abstract: Both sleep loss and pathogens can enhance brain inflammation, sleep, and sleep intensity as indicated by electroencephalogram delta (δ) power. The pro-inflammatory cytokine interleukin-1 beta (IL-1β) is increased in the cortex after sleep deprivation (SD) and in response to the Gram-negative bacterial cell-wall component lipopolysaccharide (LPS), although the exact mechanisms governing these effects are unknown. The nucleotide-binding domain and leucine-rich repeat protein-3 (NLRP3) inflammasome protein comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 52 publications
0
52
0
Order By: Relevance
“…Recently, growing lines of evidence had demonstrated that SD could trigger neuroinflammation and then resulted in neurobehavioral alterations including memory impairments (Xia et al, 2017;Zielinski et al, 2017). It was reported that pro-inflammatory cytokines such as IL-1β, TNF-α, IL-6 are found to be increased upon SD in humans as well as experimental animals, and activation of NF-κB was shown in cortex and hippocampus regions of CSD rat (Manchanda, Singh, Kaur, & Kaur, 2018;Wadhwa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing lines of evidence had demonstrated that SD could trigger neuroinflammation and then resulted in neurobehavioral alterations including memory impairments (Xia et al, 2017;Zielinski et al, 2017). It was reported that pro-inflammatory cytokines such as IL-1β, TNF-α, IL-6 are found to be increased upon SD in humans as well as experimental animals, and activation of NF-κB was shown in cortex and hippocampus regions of CSD rat (Manchanda, Singh, Kaur, & Kaur, 2018;Wadhwa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…EtOH can also effect microglial activation by altering the production and the activity of the inflammasome through the JAK/STAT signaling pathway. IL‐1β, IL‐18, HGMB1, and STAT have all been shown to be affected by EtOH and to alter neuronal excitability (Krueger et al, ; Kubota et al, ; Zielinski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of mature IL-1β, of NLRP-3 on spontaneous sleep and homeostatic sleep response following sleep deprivation (SD), NLRP-3 knockout (KO) mice showed no significant differences in IL-1β expression in the somatosensory cortex as well as caspase-1 activity following 6 h of SD compared with baseline, whereas wild-type mice showed elevated caspase-1 activity and NLRP-3, ASC, and IL-1β expression. 19 In the same study, NLRP-3 KO mice also showed reduced NREM sleep during the light period, and their homeostatic sleep responses following SD were attenuated. These findings suggest NLRP-3 activation as an important molecular mechanism for regulating SD-induced sleep response.…”
Section: Sf Induced Up-regulation Of the Nlrp-3 Complexmentioning
confidence: 85%